Microwave-assisted reactions of allenic esters: [3+2] annulations and allenoate-Claisen rearrangement - Lopes, Susana M. M. (2009)
The reactivity of allenic esters towards an activated N-sulfonylimine and electron-deficient alkenes with a phosphine under microwave irradiation is explored. The methodology is shown to be efficient for the one-step synthesis of 3-pyrrolines and cyclopentenes in a regio- and diastereoselective manner. This formal [3+2] cycloaddition is complete within five minutes. It was also demonstrated that microwave irradiation is the best energy source to carry out the Lewis acid catalyzed allenoate-Claisen rearrangement leading to 3-(pyrrolidin-1-yl)hepta-2,6-dienoates.